Precipitation of Heavy Metal Ions (Cu, Fe, Zn, and Pb) from Mining Flotation Effluents Using a Laboratory-Scale Upflow Anaerobic Sludge Blanket Reactor - Leal-Gutiérrez, Manuel José; Cuéllar-Briseño, Rodrigo; Castillo-Garduño, Andrei M.; Bernal-González, Marisela; Chávez-Castellanos, Ángel Enrique; Solís-Fuentes, Julio Alberto; Durán-Domínguez-de-Bazúa, María-del-Carmen; Bazúa-Rueda, Enrique Rodolfo (Water, air, and soil pollution, 2021)
Metal mining extraction and concentration need water. The recycling of liquid effluents reduces its consumption. This recycled water must contain low concentrations of metals. This project’s first objective was to start up a laboratory-scale upflow anaerobic sludge blanket (UASB) reactor for biotransforming metal sulfates into metal sulfides of effluent from flotation units of a mining plant (FE). The second objective was to determine the effect of pH and chemical oxygen demand:sulfate ratio (COD:SO 4 2− ) in the precipitation of heavy metal sulfides. The third objective, which is the subject of this part of the research, was to evaluate the feasibility of this proposal through a mass balance of the metals separated by precipitation through the formation of sulfides by sulfate-reducing microorganisms (SRM), using as energy source carbonaceous compounds from flotation residual organic reagents enriched with lactic acid. To monitor bioconversion effectiveness, various parameters were used: pH-alkalinity factor (α), temperature (T), COD, SO 4 2− , and sulfides (S 2− ). Four metals were considered for this part of the research: Cu, Pb, Zn, and Fe. The UASB system achieved a sulfate bioconversion of 69% and an organic matter removal as COD of 88% after transient state with the best COD:SO 4 2− ratio found. Using a statistical analysis by clusters, metal sulfide production of 74 mg L −1 and removals of 39, 70, 79, and 65%, for Pb, Cu Zn, and Fe, respectively, were obtained. These values were calculated with an initial ratio of COD:SO 4 2− of 0.66 ± 0.2 and pH values around 6 inside the reactor, through anaerobic microbial biomass, indicating that the solution proposed to recycle water in the metal extraction and concentration is feasible after using these systems.